The association between prehospital care and in-hospital treatment decisions in acute stroke: a cohort study. Issue 2 (7th October 2013) - Sheppard, James P; Mellor, Ruth M; Greenfield, Sheila; Mant, Jonathan; Quinn, Tom; Sandler, David; Sims, Don; Singh, Satinder; Ward, Matthew; McManus, Richard J
Abstract : Background: Hospital prealerting in acute stroke improves the timeliness of subsequent treatment, but little is known about the impact of prehospital assessments on in-hospital care. Objective: Examine the association between prehospital assessments and notification by emergency medical service staff on the subsequent acute stroke care pathway. Methods: This was a cohort study of linked patient medical records. Consenting patients with a diagnosis of stroke were recruited from two urban hospitals. Data from patient medical records were extracted and entered into a Cox regression analysis to investigate the association between time to CT request and recording of onset time, stroke recognition (using the Face Arm Speech Test (FAST)) and sending of a prealert message. Results: 151 patients (aged 71±15 years) travelled to hospital via ambulance and were eligible for this analysis. Time of symptom onset was recorded in 61 (40%) cases, the FAST test was positive in 114 (75%) and a prealert message was sent in 65 (44%). Following adjustment for confounding, patients who had time of onset recorded (HR 0.73, 95% CI 0.52 to 1.03), were FAST-positive (HR 0.54, 95% CI 0.37 to 0.80) or were prealerted (HR 0.26, 95% CI 0.18 to 0.38), were more likely to receive a timely CT request in hospital. Conclusions: This study highlights the importance of hospital prealerting, accurate stroke recognition, and recording of onset time. Those not recognised with stroke in a prehospital setting appear to be excluded from the possibility of rapid treatment in hospital, even before they have been seen by a specialist.